Sur la modélisation des ondes élastiques dans les structures : calculs adaptatif et parallèle avec équilibrage de charges - Tie, Bing; Aubry, Denis; Leclère, Jean-Michel (European Journal of Computational Mechanics, 2002)
The numerical modelling of middle and high frequency elastic wave propagation in engineering structures often leads to the use of very fine and very expansive finite element models. To develop more reliable and efficient numerical tools for this issue, the adaptive finite element method offers the advantages of locally refined finite element meshes around the wave fronts in an automatically controlled way. Furthermore, the parallel computing proposes a natural way to reduce the computation time and increase the capacity of computers by duplicating processors. The aim of this paper is to propose a global approach which couples the adaptive and the parallel computations for the structural transient analysis. An adaptive and dynamic load balancing strategy is defined. The space-time discontinuous Galerkin method is used in order to assume appropriate frameworks for the adaptive remeshing procedure. A new domain decomposition method is proposed which uses two levels of hierarchical finite element meshes and leads to the scalability of the parallel computation. Several numerical results are presented to show the feasability of our approach.